The Preferences Of Mobile Contents Reguired By Consumers And Factory Influencing The Choice Of Mobile Contents By Different Types Of Consumers - Xin, Lim Ke (2004)
As mobile technology develops, the potential for mobile content grows, offering new neans which engage customers interact with tier mobiles in a more complex and interesting ways. Although with the fast growing trends of mobile contents development, the mobile operators still are facing failure in delivering some of the mobile contents in Malaysia and South Korea. The response is low for some of the mobile content services. Hence, it is important for the mobile operators to understand the consumer behaviour in adopting mobile contents using TAM model.